Pedagogical Competence in Brigada Pagbasa: Basis for A Proposed Training Manual - Catarman, Marylyn B.; Liquido, Ma. Gloria E. (Randwick International of Education and Linguistics Science Journal, 2025)
This study investigated the pedagogical competence of teachers in decoding, phonics instruction, and contextual understanding and its relationship with the FLAT performance of Grades 1, 2, and 3 learners in Las Nieves District 1. The study utilized secondary data from the FLAT performances during the 1st and 2nd quarters of SY 2023-2024, involving 250 Grade 1, 100 Grade 2, and 100 Grade 3 pupils. A researcher-made instrument validated by experts and tested for reliability was used to assess the pedagogical competence of teachers. The results showed that teachers' competence in developing decoding skills and phonics instruction was excellent across all grades. The competence in contextual understanding was rated as very satisfactory. A significant relationship was found between the FLAT performance of Grade 1 pupils and teachers' competence in decoding (ρ= .238; p=.000), phonics instruction (ρ=.209; p=.001), and contextual understanding (ρ=.235; p=.000. Similarly, for Grade 2 pupils, their FLAT performance showed a very significant relationship with teachers' competence in decoding (ρ= .238; p=.000), phonics instruction (ρ=.209; p=.001), and contextual understanding (ρ=.235; p=.000). However, for Grade 3 pupils, no significant relationship was found between their FLAT performance and teachers' pedagogical competence, as indicated by p-values beyond the .05 level of significance